EFL TEACHERS’ AND LEARNERS’ PERSPECTIVE ON TEACHERS’ ONLINE WRITTEN FEEDBACK - Lailatus - Sa'adah; Rosi - Anjarwati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
Feedback plays an important role in EFL classroom for both learners and teachers. Many theoreticians and practitioners in the field of education paid attention to the used of feedback in learning. The aim of this study is to know how EFL teacher provide written feedback in response to the learners’ work and how the learners’ perspective toward the teachers’ written feedback during pandemic through online learning. To obtain the data for this study, a mixed method research design is used since it needs both qualitative and quantitative data. Some instruments is used to collect the data of this study are the students’ graded compositions to identify the nature of the feedback provided and a close-ended questionnaire was given to the participant EFL students in order to gain insight into their opinions and attitudes to their teacher’s feedback. The result reveals that the teachers provided many indirect feedbacks for their students that mostly focused on the content of their writing and sometimes on their grammar, vocabulary, and spelling. Most of the students have possitive impression and feeling as they interested and satisfied with the teachers’ feedback.